Ultrasound-derived skinfolds in anthropometric predictive equations overestimate fat mass: A validation study using a four-component model - Cerullo, G.; Franchi, M. V.; Sampieri, A.; Campa, F.; Paoli, A. (Nutrients, 2025)
Background: The evaluation of body composition is considered a key factor for assessing nutritional status. In several settings, ultrasound (US) has been used as a useful tool in nutritional practice by estimating body composition parameters, such as the whole-body fat mass (FM). The estimation of FM can be carried out by using predictive equations that generally require measurements of skinfold thickness, which can be measured directly via US imaging. The main aim of this study was to evaluate the validity of US-derived skinfolds within anthropometric equations for estimating whole-body FM.